Pengaruh Penggunaan Informasi Akuntansi Dan Lama Usaha Terhadap Keberhasilan Usaha Kecil Menengah Di Desa Purwodadi Simpang - Muhammad Luthfi; Apip Alansori; Anggis Novitania (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
Economic development in Indonesia is generally based on the people's economy, which can be seen in the Micro, Small and Medium Enterprises (MSMEs) sector. This sector has a large role in the regional economy and the national economy. The use of accounting information and length of business are believed to be able to influence business success.This study aims to determine whether the use of accounting information and length of business have a direct significant effect on business success. The population in this study were 30 SMEs in Purwodadi Simpang Village. Data collected by questionnaire technique. The data analysis technique used is Multiple Linear Regression Analysis using the SPSS version 29 program.The results of this partial test indicate that the use of accounting information has a significant effect, and length of business has no significant effect on business success. While the results of the simultaneous test show that the use of accounting information on long-term funds has a significant effect on business success in Purwodadi Simpang Village.